Dual B Cell Immunotherapy Is Superior to Individual Anti‐CD20 Depletion or BAFF Blockade in Murine Models of Spontaneous or Accelerated Lupus. Issue 1 (January 2015) - Lin, WeiYu; Seshasayee, Dhaya; Lee, Wyne P.; Caplazi, Patrick; McVay, Sami; Suto, Eric; Nguyen, Allen; Lin, Zhonghua; Sun, Yonglian; DeForge, Laura; Balazs, Mercedesz; Martin, Flavius; et al.
<x xml:space="preserve">Abstract</x> Objective To determine whether a combination of B cell depletion and BAFF blockade is more effective than monotherapy in treating models of spontaneous or accelerated systemic lupus erythematosus (SLE) in (NZB × NZW)F1 mice. Methods Clinical parameters such as disease progression–free survival, proteinuria, and renal injury were assessed in models of spontaneous, interferon‐α (IFNα)–accelerated, or pristane‐accelerated lupus in (NZB × NZW)F1 mice. Treatment arms included anti‐CD20 (B cell depletion), B lymphocyte stimulator receptor 3 fusion protein (BR‐3‐Fc) (BAFF blockade), the combination of anti‐CD20 and BR‐3‐Fc, isotype control, or cyclophosphamide. In models of spontaneous, IFNα‐accelerated, or pristane‐accelerated lupus, mice were treated for 24 weeks, 8 weeks, or 12 weeks, respectively. Peripheral and resident B cell subsets and various autoantibodies were examined. Results Compared to B cell depletion or BAFF blockade alone, combined therapy significantly improved disease manifestations in all 3 lupus models. In addition, marginal zone B cells, plasmablasts, and circulating and tissue plasma cells were decreased more effectively. Dual B cell immunotherapy also reduced multiple classes of pathogenic autoantibodies, consistent with its observed effectiveness in reducing immune complex–mediated renal injury. Conclusion Dual immunotherapy via B cell depletion and BAFF blockade is more efficacious than single agent immunotherapy in murine SLE models, and this combination treatment is predicted to be an effective strategy for immunotherapy in human SLE.